Prediction of pre-eclampsia: role of placental laterality by ultrasonography - Kore, Shailesh Janardhan; Khot, Rohit; Supe, Pradnya; Kanavia, Divya; Thunga, Chaitra; Nandanwar, Yogeshwar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pre-eclampsia, the most common medical complication of pregnancy, continues to be one of the leading causes of maternal morbidity and mortality. Women with mild and moderate degrees of gestational hypertension can often be treated conservatively and delivered at or near term with good perinatal outcome. The objective of this study was to find out whether placental laterality as determined by ultrasound done between 20-24 weeks can be used as a predictor of development of preeclampsia. Methods: In this prospective study, a total of 200 low risk singleton pregnant women attending the antenatal clinic at tertiary teaching institute were included. The location of the placenta was determined by ultrasound at 20-24 weeks. The women were divided into two groups- group A with Central placenta and group B with Lateral placenta. The end point of the study was the development of preeclampsia as per the ACOG criteria or delivery. Results: Out of 200 antenatal women, 161 had central placenta (Group-A) and 39 had unilateral placenta (Group-B). A total of 32 women developed preeclampsia, of which 19 (59.38%) had unilaterally located placenta at 20-24 weeks. This relationship was statistically highly significant (P<0.0001). The sensitivity, specificity, positive predictive value and negative predictive value of using placental laterality as a screening test were 59.38%, 88.10%, 48.72% and 91.93% respectively. Conclusions: Placental laterality as determined by ultrasound at 20-24 weeks; is a simple yet reliable and cost effective predictive screening test for development of preeclampsia.